Comparative glycomic profiling of isotopically permethylated N‐glycans by liquid chromatography/electrospray ionization mass spectrometry. (12th March 2013) - Hu, Yunli; Desantos‐Garcia, Janie L.; Mechref, Yehia
<x xml:space="preserve">Abstract</x> RATIONALE Mass spectrometry based comparative glycomics is essential for disease biomarker discovery. However, developing a reliable quantification method is still a challenging task. METHODS We here report an isotopic labeling strategy employing stable isotopic iodomethane for comparative glycomic profiling by liquid chromatography/electrospray ionization mass spectrometry (LC/ESI‐MS). N‐Glycans released from model glycoproteins and blood serum samples were permethylated with iodomethane ('light') and iodomethane‐d1 or ‐d3 ('heavy') reagents. Permethylated samples were then mixed at equal volumes prior to LC/ESI‐MS analysis. RESULTS Peak intensity ratios of N‐glycans isotopically permethylated (Heavy/Light, H/L) were almost equal to the theoretical values. Observed differences were mainly related to the purity of 'heavy' iodomethane reagents (iodomethane‐d1 or ‐d3). The data suggested the efficacy of this strategy to simultaneously quantify N‐glycans derived from biological samples representing different cohorts. Accordingly, this strategy is effective in comparing multiple samples in a single LC/ESI‐MS analysis. The potential of this strategy for defining glycomic differences in blood serum samples representing different esophageal diseases was explored. CONCLUSIONS LC/ESI‐MS comparative glycomic profiling of isotopically permethylated N‐glycans derived from biological samples and glycoproteins reliably defined glycan changes associated with biological conditions or glycoproteins expression. As a biological application, this strategy permitted the reliable quantification of glycomic changes associated with different esophageal diseases, including high grade dysplasia, Barrett's disease, and esophageal adenocarcinoma. Copyright © 2013 John Wiley & Sons, Ltd.